Cellular Events of Multinucleated Giant Cells Formation During the Encystation of Entamoeba invadens - Krishnan, Deepak; Ghosh, Sudip K. (Frontiers in Cellular and Infection Microbiology, 2018)
Entamoeba histolytica, the causative agent of amoebiasis, does not form cysts in vitro, so reptilian pathogen Entamoeba invadens is used as an Entamoeba encystation model. During the in vitro encystation of E. invadens, a few multinucleated giant cells (MGC) were also appeared in the culture along with cysts. Like the cyst, these MGC's were also formed in the multicellular aggregates found in the encystation culture. Time-lapse live cell imaging revealed that MGC's were the result of repeated cellular fusion with fusion-competent trophozoites as a starting point. The early MGC were non-adherent, and they moved slowly and randomly in the media, but under confinement, MGC became highly motile and directionally persistent. The increased motility resulted in rapid cytoplasmic fissions, which indicated the possibility of continuous cell fusion and division taking place inside the compact multicellular aggregates. Following cell fusion, each nucleus obtained from the fusion-competent trophozoites gave rise to four nuclei with half genomic content. All the haploid nuclei in MGC later aggregated and fused to form a polyploid nucleus. These observations have important implications on Entamoeba biology as they point toward the possibility of E. invadens undergoing sexual or parasexual reproduction.